(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
The focus of this paper is to design and develop the Artificial Intelligence and Machine Learning based system which detects the fungal infection on a pet animal (especially Dog and Cat), and provide the treatment for it. It also provides the causes, Symptoms, Prevention for it. The proposed system integrates on Machine Learning algorithm trained on disease dataset, it first detects the species of pet animal by capturing the image of fungal infection of pet by using camera or by uploading the image in the system from the file explorer, and then provide the diagnosis about the fungal disease and its medication and treatment also. Although our system will verify the scan image for determining the diseases in canine. Diagnosing the Fungal Infection on pet animal quickly and accurately has the economic effectiveness.